An analytical method for determining the tensile membrane action of RC slab panels. (15th October 2021) - Wang, Yong; Wang, Gongchen; Huang, Zhaohui; Huang, Yuner; Jiang, Yaqiang; Zhang, Yajun; Zhang, Cong; Bu, Yixiang; Song, Wei
Highlights: Develop an analytical method to predict the ultimate loads and deflection of the two-way supported concrete slabs. The prediction of the method is agreed well with the test and numerical results. The developed method can be used for predicting the ultimate loads and failure modes of the two-way simply supported RC slabs at large deflections. The method can reasonably predict the tensile membrane action region and failure modes of the two-way concrete slabs. Abstract: This paper presents a newly developed method for determining the influence of tensile membrane action on the ultimate loading capacity of a two-way RC concrete slab. In this method, more realistic membrane action and two failure criteria of a slab panel are established. The developed method has been validated against the test results and good agreement is achieved. Compared to the tensile membrane action region obtained from the FEM (Vulcan), the assumptions about the focus of the ellipse equation proposed within the present method are reasonable and accurate. The present method can be used for predicting the ultimate loads and failure modes of the two-way simply supported RC slabs at large deflections. The research indicates that the in-plane shear force has considerable effect on the prediction of ultimate loads of the slabs and neglecting the in-plane shear force results the overestimated the concrete corner strains.